SISTEM PENANGGALAN SUKU NIAS DALAM PERSPEKTIF ASTRONOMI - Arisafitri, Novi; Izzuddin, Ahmad (UIN ALAUDDIN MAKASSAR, 2021)
The presence of a calendar or calendar is the most famous and urgent legacy of human civilization for human survival. One of the indigenous Indonesian tribes has a local calendar that is relatively different from the general calendar, namely the Nias tribe. Traditional Nias people used to not know the clock, the division and naming of their time refers to daily activities such as raising livestock, farming, domestic work and other natural phenomena. The traditional Nias people besides having a daily time reference, they also have a calendar system used for agricultural activities that refers to the circulation of the Orion Star or based on local wisdom the Nias people call it Bintang Sara Wangahalö.